Profil Kromatografi Dan Penentuan Kadar Flavonoid Total Fraksi N-Heksan Daun Kalangkala (Litsea angulata Bl) Menggunakan Spektrofotometri UV-Vis: Profil Kromatografi Dan Penentuan Kadar Flavonoid Total Fraksi N-Heksan Daun Kalangkala (Litsea angulata Bl) Menggunakan Spektrofotometri UV-Vis - Rohama Rohama; Setia Budi; Puspita Astuti (LPPM Universitas Sari Mulia, 2023)
ABSTRACTBackground: Kalangkala (Litsea angulata Bl) is a typical plant of South Kalimantan which is empirically used by the community in the treatment of boils. One of the compounds contained is flavonoids, flavonoids have many pharmacological activities, one of which is as an antibacterial. Flavonoids can be extracted with several solvents based on the level of polarity, one of which is n-hexane which has non-polar properties.Objective: To determine the chromatographic profile and total flavonoid content of the n-hexane fraction of Kalangkala (Litsea angulata Bl) leaves by using the UV-Vis Spectrophotometry method.Methods: This study used an analytical observational method to determine the chromatographic profile of flavonoids and descriptive observation in determining the total flavonoid content of the n-hexane fraction of Kalangkala (Litsea angulata Bl) leaf using UV-Vis Spectrophotometry.Results: The results of the identification of the compound showed that the leaves of Kalangkala (Litsea angulata Bl) were positive for flavonoids. Meanwhile, in the chromatographic profile, the eluent capable of detecting flavonoid compounds was n-Hexane: Ethyl acetate (8:12) with seven stains. The results of the determination of the total flavonoid content of the n-hexane fraction of Kalangkala leaves (Litsea angulata Bl) was 8,367 mg QE (Quersetin Equivalent)/g.Conclusion: Thin Layer Chromatography (TLC) of the n-Hexane fraction of Kalangkala leaves (Litsea angulata Bl) showed flavonoid compounds with the best eluent n-Hexane: Ethyl acetate (8:12) and the total flavonoid content of the n-Hexane fraction of Kalangkala (Litsea angulata Bl) was 8,367 mg QE(Quercetin Equivalent)/g.Keywords: Litsea angulata Bl, Total Flavonoid, n-Hexane